The lytic bacteriophage vB_EfaH_EF1TV, a new member of the Herelleviridae family, disrupts biofilm produced by Enterococcus faecalis clinical strains. (June 2020) - D'Andrea, Marco Maria; Frezza, Domenico; Romano, Elena; Marmo, Pasquale; Henrici De Angelis, Lucia; Perini, Nicoletta; Thaller, Maria Cristina; Di Lallo, Gustavo
Graphical abstract: Highlights: EF1TV is a newly discovered lytic bacteriophage specific for Enterococcus faecalis . Phage EF1TV is the fourth characterized member of the Kochikohdavirus genus within the Herelleviridae family. EF1TV disrupts biofilm produced by strains of Enterococcus faecalis, even if they are not able to produce productive infection. Integrity of the enterococcal polysaccharide antigen gene cluster is necessary for the infectivity of EF1TV. Abstract: Objectives: The aim of this study is to characterize a new bacteriophage able to infect Enterococcus faecalis, and to evaluate its ability to disrupt biofilm. Methods: The vB_EfaH_EF1TV (EF1TV) host-range was determined by spot test and efficiency of plating using a collection of 15 E. faecalis clinical strains. The phage genome was sequenced with a next generation sequencing approach. Anti-biofilm activity was tested by crystal violet method and confocal laser scanning microscopy. Phage-resistant mutants were selected and sequenced to investigate receptors exploited by phage for infection. Results: EF1TV is a newly discovered E. faecalis phage which belongs to the Herelleviridae family. EF1TV, whose genome is 98% identical to φEF24C, is characterized by a linear dsDNA genome of 143, 507 bp with direct terminal repeats of 1, 911 bp. The phage is able to infect E. faecalis and shows also the ability to degrade biofilm produced by strains of this species. The results were confirmed by confocal laser scanning microscopy analyzing the biofilm reduction in the same optical field before and after phage infection. Conclusions: The EF1TV phage shows promising features such as an obligatory lytic nature, an anti-biofilm activity and the absence of integration-related proteins, antibiotic resistance determinants and virulence factors, and therefore could be a promising tool for therapeutic applications.